Pre- and Post-Harvest Management Linked with Aflatoxin Contamination of Maize in Different Ecologies of Nepal. - Devkota, Mina.; Shrestha Ravindra.; McDonald, Andrew. (Tufts University. Tisch Library., 2019)
This presentation was from 6th Annual scientific Symposium in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy